Drivers of learning and development effectiveness of organizations in Malaysia - Rampal, Arvind (Arvind Rampal, 2020)
The current study looks at the drivers of learning and development effectiveness for companies in Malaysia. The learning and development function is viewed to be ineffective and not meeting organizational objectives in improving performance. Companies are investing millions into training without seeing a return on investment. In this study the impact of the variable drivers for Training, Organizational Learning, Leadership and HR policies on the effectiveness of learning and development programs in Malaysia are researched. The research is based on the responses of individuals, a sample size of 100 that came back with their feedback to the questions. A quantitative analysis was carried out to understand the strength of the relationship of the variables and the direction of the relationship. The methodology consisted of using an appropriate sampling method. Overall the results conclude that all these variables have an impact on effectiveness of learning and development programs in Malaysia. This coincides with other studies, which have concluded the impact of each of these variables separately. The way forward and most prominent recommendation is that organizations need to take a holistic and systematic approach to strategizing it’s learning and development initiatives and plans with the support of best practices in Training, Organizational Learning, Leadership and HR policies.